(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1996)
The aim of this paper is to build an orthogonal system in L_2, consisting of functions of a given fractal dimension. It is a tool for approximation of objects of certain fractal dimension. Here only the one-dimensional case is approached, however the considerations could be easily transferred to case of higher dimension.